A Feasible Study on the Privatization of Public Libraries: a SWOT Analysis Approach (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی, 2013)
Purpose: This study identifies  the most important internal factors of strengths and Weaknesses, as well as the external factors of opportunities and threats in regards with privatization of the public libraries, and their readiness for  privatization. Methodology: the factors and variables resulted from a literature review and several interviews with a group of experts in the field of library and information science. The  researcher's observations were used to analyze the internal and external SWOT factors in regards with privatization in public libraries. Findings: Findings show that the public libraries under the study are quite ready for privatization both internally, and externally, provided that they take advantage of opportunities they have. The  weighted sum of the strengths and weaknesses is 3.38, and the weighted sum of opportunities and threats is 3.47, both of which are greater than the cut point 2.50. Originality/Value: this seems to be the first attempt in SWOT analysis of public libraries in regards with privatization of these libraries.